A behaviourally informed heuristics-framework for net zero transformation in manufacturing - Kaur, Rashmeet; Patsavellas, John; Salonitis, Konstantinos (Springer, 2024)
Transitioning to net zero emissions in manufacturing is fraught with challenges, from navigating uncertainties and making critical trade-offs, to overcoming biases and information asymmetry. Such behavioural challenges could potentially result in bounded rationality, where decision-makers operate under limited information and cognitive constraints. This paper introduces a framework that employs behaviourally informed heuristics to simplify the complexity of net-zero transformation. By incorporating behavioural model of rational choice and decision-making rules, the framework could help manufacturing decision-makers to manage uncertainties and cognitive limitations, thus broadening the toolkit for navigating the reduction of carbon emissions.
Keywords: Net zero manufacturing; Transformational framework; Bounded rationality